Evaluation of Amino Acid and Vitamin B2 and E Composition of Genetically Modified Antidwarf Mosaic Maize by Automatic Amino acid Analyzer and HPLC - Yan, Pingmei; Wang, Qing; Yan, Xiaoyan; Chang, Xiao-Hui; Du, Jian-Zhong; Sun, Yi (Asian Journal of Chemistry, 2013)
The nutrition assessment of transgenic food is an important part of safety evaluation. The amino acids and vitamins composition of genetically modified antidwarf mosaic maize were comprehensively evaluated to assess the safety assessment of transgenic food. The results showed that the most components of transgenic corn had no significant difference from those of non-transgenic, which proved that genetically modified antidwarf mosaic maize is safe. But the contents of vitamin E and three amino acids in transgenic corn had significant difference from its parent variety, so genetically modified crops must undergo a rigorous safety test before as a food.